Novel approach to decision making for orphan drugs - Decker, Barbora; Mlcoch, Tomas; Pustovalova, Anastasie; Dolezal, Tomas (International journal of technology assessment in health care, 2023)
BACKGROUND: Out of 185 orphan medicinal products (OMPs) registered in 2015-2021, a mere 110 (59 percent) were available to Czech patients, and only 54 (29 percent) were officially reimbursed. Moreover, this proportion has steadily decreased over time. After years of public debate induced by this unsatisfactory OMP patient access, the national viewpoint shifted toward creating a special pathway for the reimbursement of OMP. Thus, a rigorous pricing and reimbursement procedure with strict timelines and elaborated methodology has been recently adopted in Czechia. METHODOLOGY: The innovative legislation follows the recommendations for value assessment and funding processes for rare diseases and incorporates additional elements of value, such as the societal perspective. First, the application with clinical evidence, cost-effectiveness, and budget impact analyses is submitted to the governmental health technology assessment (HTA) agency by the Marketing Authorization Holder or a Health Insurance Fund. Moreover, professional associations and patients' organizations are rightful participants in the proceeding, providing evidence and comments. Then, the HTA agency performs the assessment/appraisal of the evidence. It subsequently publishes the assessment report summarizing available information. The report is then forwarded to the Ministry of Health and its advisory body consisting of patients, clinical experts, health insurance funds, and the State. They critically evaluate the documents and issue a binding opinion following prespecified decision-making criteria. Based on this binding opinion, the decision is issued by the HTA agency. Thus, the role of the advisory body in this process is crucial. CONCLUSION: We believe that this novel approach may offer satisfactory patient access to orphan drugs. Moreover, it serves as a real-world example of "value-based" decision making.
Keywords: Orphan Drug Production; úhrada zdravotního pojištění; výroba orphan drugs; Česká republika; lidé; vzácné nemoci; Rare Diseases; Technology Assessment, Biomedical; Humans; Insurance, Health, Reimbursement; rozhodování; hodnocení biomedicínských technologií; Decision Making; Czech Republic